Pemberdayaan Remaja Melalui Pelatihan Hormonal Awareness dan Kesehatan Reproduksi Berbasis Display Model 3D Fase Hormonal - Friscila, Ika; Rizali, Muhammad; Wijaksono, M. Arief; Fitriani, Aida (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2025)
Adolescence represents a critical phase of development, particularly concerning hormonal changes and reproductive health. It was observed that several female students were unable to accurately track their menstrual cycles, sometimes necessitating their early dismissal from school due to Premenstrual Syndrome (PMS). Open discussion regarding reproductive health content remains infrequent, with students often reporting feelings of awkwardness and a lack of confidence in engaging in such discussions. The program's primary objectives were to enhance awareness and understanding of hormonal phases and sexually transmitted infections (STIs), and to develop display model 3D-based educational media as a visual and interactive aid for comprehending the hormonal system. The activity was conducted at Senior High School, involving 80 female students as participants. The socialization material covered hormonal phases and STIs. To assess the level of understanding, pre- and post-tests were administered. The results indicated a significant increase in knowledge following the intervention. A key outcome of this program was the production and dissemination of new 2- and 3-dimensional hormonal display model designs, which were subsequently integrated as learning materials.